EFFECT OF REWARD AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE THROUGH WORK SATISFACTION AS A MEDIATION (STUDY ON EMPLOYEES OF PT. INTERNATIONAL CHEMICAL INDUSTRY) - Apriyanti, Rina; R Sudiarditha, I Ketut; Saptono, Ari (Dinasti Publisher, 2021)
As a provider of battery products under the ABC brand name, PT International Chemical Industry always strives to improve the performance of its employees in order to maintain existing market share. However, the problem faced in this study is about the quality of employee performance during the 2015-2019 period, during which the employee's performance did not comply with the standards set by the company and inconsistencies occurred which resulted in not achieving the company's production targets, even though the company had completed policies regarding company performance standards. This study aims to examine and analyze the effect of reward, and work environment, on employee performance through job satisfaction. This research is quantitative in nature using multivariate analysis with SEM LISREL tools. Withdrawal of population using census techniques, the sample of respondents is permanent employees totaling 420. The results of this study indicate a positive and significant effect of reward on job satisfaction, a positive and significant effect of the work environment on job satisfaction, a positive and significant effect of reward on job satisfaction. Employee job satisfaction, there is a positive and significant influence of the work environment on employee performance, there is a positive and significant influence of job satisfaction variables on employee performance.